Differentially expressed protein and gene analysis revealed the effects of temperature on changes in ascorbic acid metabolism in harvested tea leaves. Issue 1 (1st October 2018) - Li, Hui; Liu, Zhi-Wei; Wu, Zhi-Jun; Wang, Yong-Xin; Teng, Rui-Min; Zhuang, Jing
Abstract: Tea is an important non-alcoholic beverage worldwide. Tea quality is determined by numerous secondary metabolites in harvested tea leaves, including tea polyphenols, theanine, caffeine, and ascorbic acid (AsA). AsA metabolism in harvested tea leaves is affected by storage and transportation temperature. However, the molecular mechanisms underlying AsA metabolism in harvested tea leaves exposed to different storage and transportation temperature conditions remain unclear. Here we performed RP-HPLC to detect dynamic changes in AsA content in tea leaves subjected to high- (38 °C), low- (4 °C), or room-temperature (25 °C) treatments. The AsA distribution and levels in the treated tea leaves were analyzed using cytological–anatomical characterization methods. The differentially expressed CsAPX1 and CsDHAR2 proteins, which are involved in the AsA recycling pathway, were identified from the corresponding proteomic data using iTRAQ. We also analyzed the expression profiles of 18 genes involved in AsA metabolism, including CsAPX1 and CsDHAR2 . AsA was mainly distributed in tea leaf mesophyll cells. High- and low-temperature treatments upregulated the CsAPX1 and CsDHAR2 proteins and induced CsAPX and CsDHAR2 gene expression. These results indicated that the CsAPX1 and CsDHAR2 proteins might have critical roles in AsA recycling in tea leaves. Our results provide a foundation for the in-depth investigation of AsA metabolism in tea leaves during storage and transportation, and they will promote better tea flavor in tea production. Tea: storage temperature impacts vitamin C metabolism: High and low temperatures induce the expression of enzymes involved in vitamin C metabolism in tea leaves. A research team from Nanjing Agricultural University, China, led by Jing Zhuang collected fresh leaves from 1-year-old tea plants of the Longjing #43 varietal and then stored the leaves for 4 h at 4 °C (cold), 38 °C (hot), or 25 °C (room temperature). They found that absolute levels of vitamin C—an antioxidant molecule also known as ascorbic acid—were highest after storage at the low temperature and lowest after storage at the high temperature. However, the expression levels of genes involved in vitamin C synthesis and breakdown were elevated at both high and low temperatures. The findings could aid the tea industry in developing storage and transportation strategies that optimize leaf quality and flavor.